If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 + 4x = -42 Solving -10 + 4x = -42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 4x = -42 + 10 Combine like terms: -10 + 10 = 0 0 + 4x = -42 + 10 4x = -42 + 10 Combine like terms: -42 + 10 = -32 4x = -32 Divide each side by '4'. x = -8 Simplifying x = -8
| 0.88=log(x) | | 2(9x+631)=2x+270 | | .88=log(x) | | 1-5b-4b=10 | | 11z=-100 | | 3n-9+3=24 | | 3(14-4y)-5y=-9 | | 6y+5=10y-1 | | 12k+14=10k-2k-7 | | -3(x+4)+16= | | J-8=-5 | | 10x-8=31.5 | | 2(2x-11)=2x | | 8x-4+8x-4+21+3=180 | | 9x^2-42x+37=0 | | 11-3(x+4)+5= | | H-41=13 | | 24=3(x)-6 | | (10x+36y)+(2x+y)= | | 63=60.50p+17.50 | | 8x-4+8x-4+4+3=180 | | 9=3(x)-6 | | 152+8h= | | 19=b-3 | | -3=3(x)-6 | | -6.5z+7.5z= | | 4n-2=12-4n | | 7(15x+25y)=125 | | x^2+4y^2=144 | | -12=3(x)-6 | | 12x+6=4x-20-2 | | 5+3y=30 |